2019
DOI: 10.1002/aqc.3081
|View full text |Cite
|
Sign up to set email alerts
|

Abundance, distribution and diet of the common dolphin,Delphinus delphis, in the northern Aegean Sea (Greece)

Abstract: 1. The abundance, distribution and diet of the short-beaked common dolphin were investigated as part of the first detailed study on cetacean populations in the North Aegean Sea. Since 2004, the area has been proposed by national and international entities as a marine protected area for common dolphins and other cetacean species owing to its high biodiversity.2. Abundance and distribution were investigated between 2005 and 2013 through dedicated scientific marine transect surveys, covering 14,701 km, in sea con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 30 publications
2
19
1
Order By: Relevance
“…The estimated ER values could be used as an effective baseline for future assessment of the common dolphin conservation status in the area, where an increasing trend in small-scale fishery exploitation and tourist flow have been recorded in the last few years, representing potential harmful threats for the species. The mean group size estimated for the waters south of Samos Island confirmed the pattern observed for the species in the Inner Ionian Sea Archipelago [6,32] and the Thracian Sea [35]. The small-sized aggregation of common dolphin groups is probably due to a behavioral feeding strategy caused by the distribution of prey (small pelagic fish) over many small patches in the study area [5,28,54], which leads dolphins to split into smaller groups for more efficient predation [55].…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…The estimated ER values could be used as an effective baseline for future assessment of the common dolphin conservation status in the area, where an increasing trend in small-scale fishery exploitation and tourist flow have been recorded in the last few years, representing potential harmful threats for the species. The mean group size estimated for the waters south of Samos Island confirmed the pattern observed for the species in the Inner Ionian Sea Archipelago [6,32] and the Thracian Sea [35]. The small-sized aggregation of common dolphin groups is probably due to a behavioral feeding strategy caused by the distribution of prey (small pelagic fish) over many small patches in the study area [5,28,54], which leads dolphins to split into smaller groups for more efficient predation [55].…”
Section: Discussionsupporting
confidence: 78%
“…Estimations of encounter rate, group size, density, and abundance values of D. delphis were made by the application of CDS analysis to sighting data collected during standardized surveys carried out near Samos Island, Greece (Eastern Aegean Sea), providing a comparison with analogous values estimated in similar studies carried out in other Mediterranean areas ( Table 3). The encounter rates estimated in the study area were higher than values reported for the Alborán Sea [4], in waters off Ischia Island [14], in the Inner Ionian Sea Archipelago [6,32], and in the Thracian Sea [35], indicating that the waters off the south of Samos Island are an eligible habitat for D. delphis. The estimated ER values could be used as an effective baseline for future assessment of the common dolphin conservation status in the area, where an increasing trend in small-scale fishery exploitation and tourist flow have been recorded in the last few years, representing potential harmful threats for the species.…”
Section: Discussioncontrasting
confidence: 68%
See 3 more Smart Citations